Draft Report of the Working Group on Draft Agricultural Research and Education for the Eleventh Five Year Plan (2007-2012) - Planning Commission (Planning Commission, 2007)
Science and Technology are the drivers of change in farm operations and output. New technologies which can help to enhance productivity per units of land and water are needed for overcoming the prevailing technology fatigue. Frontier technologies like biotechnology, information and communication technology, renewable energy technologies and nanotechnology provide uncommon opportunities for launching an ever-green revolution capable of improving productivity in perpetuity without ecological harm
Government of India Planning Commission
Government of India Planning Commission